Beyond Digital Citizenship - Lynn Mitchell (Middle Grades Review, 2016)
Conversations in middle school about digital citizenship tend to focus on the responsibilities of citizenship and the issues of surveillance, safety, cyberbullying, and internet etiquette. While these are important and essential conversations, digital citizenship education needs to consider youth political identity and democratic participation in digital spaces if educators wish to take full advantage of the empowering potential of participatory technology. The potential for youth to shape diverse identities through digital technologies has significant implications for youth empowerment and agency and helps dismantle reductive narratives that have tended to define middle school youth. The role of digital citizenship education must be expanded to include critical social justice education. Such a reconceptualization of digital citizenship will result in curriculum that understands and supports the role digital technologies play in the development of youth political identity and help empower young people to impact positively on political issues. Little research has been done on the convergence of youth political identity and participatory technology spaces which are designed specifically for social justice and supported by social justice pedagogical ideals. Online social justice spaces support user empowerment through critical social justice education, community building, and orientation toward social action. If the context of youth lived experience is a technological one, the expression of youth political identity and youth activism through digital pathways requires attention and support from educators interested in digital citizenship education.